Light-induced iodoperfluoroalkylation reactions of carbon-carbon multiple bonds in water - Slodowicz, Mariel Pamela (2012)
In this work we have undertaken the radical-induced addition of 1-iodo-n-perfluorobutane onto electron-rich alkenes, alkenes with electron withdrawing groups, and alkynes in water, initiated photochemically. The lack of hydrogen donor (i.e.: (Me 3Si) 3SiH) in our reaction medium facilitates a Halogen Atom-transfer reaction (HAT), affording the respective perfluorobutylated alkyl and alkenyl halides (iodides) in good yields in water. We have also found that water exerts a relevant solvent effect on the rates of perfluoroalkyl radical additions onto double and triple bonds. The stereoselectivity of the radical addition reaction of alkynes is studied. The novelty of this work relies on the photochemical generation of fluorinated radicals in water, and the Halogen Atom-transfer addition reactions of iodoperfluoroalkanes onto carbon-carbon unsaturated bonds in water induced by light.